Fault current limiting using Static Series Compensator: article / Muhammad Haslam Baseran @ Basirom - Baseran @ Basirom, Muhammad Haslam (Universiti Teknologi MARA (UiTM), 2009)
In this paper, a control scheme of the Static Series Compensator (SSC) for fault current limiting has been proposed. The apparatus injects a voltage of variable magnitude in series with a transmission line. This injected voltage is in quadrature with the line current. Under normal condition, it is controlled in order to compensate for reactance of transmission line. When a disturbance occurs, injected voltage from phase shifter is applied to damping control of generator swing. This apparatus is expected to be a promising fault current limiter by using the leakage reactance of series transformer. The proposed methods were applied to 11 busbar system to show its feasibility and capability. All simulation was done using the MATLAB version 7.6 programming.